2020
DOI: 10.1080/13603116.2020.1853256
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of an instrument measuring subjective definitions of inclusion (FEDI)

Abstract: Within educational and social discourses, the term 'inclusion' has various meanings. In both research and practice, there is no official definition of inclusion. Nevertheless, subjective definitions affect pedagogical acts. We developed the Definitions of Inclusion Questionnaire [Fragebogen zur Erfassung subjektiver Definitionen von Inklusion] (FEDI) as an economic instrument that takes subjective definitions of inclusion into account. This paper describes the construction and first psychometric evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Krischler et al (2019) found that participants with a "general individualised definition" of inclusion held significantly more positive attitudes towards inclusion than participants with other definitions. Furthermore, Scheer et al (2020) found positive correlations between a school-system, a human rights, and an ethics based perspective on inclusion, suggesting that attitudes are intertwined. However, it can be assumed that a consideration of inclusive education necessitates a consideration of concepts of disability also.…”
Section: Attitudes Towards Inclusionmentioning
confidence: 96%
“…Krischler et al (2019) found that participants with a "general individualised definition" of inclusion held significantly more positive attitudes towards inclusion than participants with other definitions. Furthermore, Scheer et al (2020) found positive correlations between a school-system, a human rights, and an ethics based perspective on inclusion, suggesting that attitudes are intertwined. However, it can be assumed that a consideration of inclusive education necessitates a consideration of concepts of disability also.…”
Section: Attitudes Towards Inclusionmentioning
confidence: 96%
“…Definiciones subjetivas de la inclusión. Este instrumento fue generado para capturar las diferentes definiciones subjetivas de la inclusión (Scheer et al, 2020). Su intención es reconocer en la investigación el desarrollo de escuelas inclusivas y la formación docente para la inclusión.…”
Section: Instrumentosunclassified
“…Authors who provide different understandings of inclusion according to these four definitions also differ significantly in their attitudes towards inclusion (Krischler et al., 2019). Furthermore, subjective understandings of inclusion can be measured by three dimensions: school system based perspectives (SSB); human‐rights / ethics based perspectives (HEB); and outcomes/achievement based perspectives (OAB)—where HEB perspectives correlate with attitudes towards inclusion (Scheer et al., 2020). Thus, research on inclusive school development should include participants' subjective understandings of inclusive education.…”
Section: Contextualisationmentioning
confidence: 99%